REPRESENTASI CITRA KEBUDAYAAN LINGKUNGAN MADURA DALAM KUMPULAN PUISI SANGKOLAN MATA CELURIT MATA SABIT KARYA ROZ EKKI - Risma Ardiyanti; Mariam Ulfa; Rozekki Rozekki (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study aims to describe the representation of cultural imagery in the poetry collection Sangkolan Mata Celurit Mata Sabit by Roz Ekki using a cultural studies perspective. This study uses a qualitative descriptive approach. The research data are in the form of words, lines, and stanzas in the poetry collection containing cultural imagery. The data collection technique is carried out through the documentation method by reading, recording, and classifying parts of the text related to environmental cultural imagery. Data analysis is carried out by interpreting symbols, imagery, and diction that represent the relationship between Madurese society and nature. The results of the study show that the image of environmental culture is depicted through natural symbols such as fields, land, sea, coastal winds, and farming and fishing activities that show the closeness of Madurese society to nature. Imagery. Thus, this collection of poetry is not only an aesthetic work, but also represents the cultural identity of Madurese society and the relationship between humans and the environment that shapes their lives.